Not all non-drinkers with HIV are equal: demographic and clinical comparisons among current non-drinkers with and without a history of prior alcohol use disorders*. Issue 2 (1st February 2017) - Crane, Heidi M.; Nance, Robin M.; Merrill, Joseph O.; Hutton, Heidi; Chander, Geetanjali; McCaul, Mary E.; Mathews, W. Chris; Fredericksen, Rob; Simoni, Jane M.; Mayer, Kenneth; Mugavero, Michael J.; Willig, James H.; et al.
ABSTRACT: Studies of persons living with HIV (PLWH) have compared current non-drinkers to at-risk drinkers without differentiating whether current non-drinkers had a prior alcohol use disorder (AUD). The purpose of this study was to compare current non-drinkers with and without a prior AUD on demographic and clinical characteristics to understand the impact of combining them. We included data from six sites across the US from 1/2013 to 3/2015. Patients completed tablet-based clinical assessments at routine clinic appointments using the most recent assessment. Current non-drinkers were identified by AUDIT-C scores of 0. We identified a prior probable AUD by a prior AUD diagnosis in the electronic medical record (EMR) or a report of attendance at alcohol treatment in the clinical assessment. We used multivariate logistic regression to examine factors associated with prior AUD. Among 2235 PLWH who were current non-drinkers, 36% had a prior AUD with more patients with an AUD identified by the clinical assessment than the EMR. Higher proportions with a prior AUD were male, depressed, and reported current drug use compared to non-drinkers without a prior AUD. Former cocaine/crack (70% vs. 25%), methamphetamine/crystal (49% vs. 16%), and opioid/heroin use (35% vs. 7%) were more commonly reported by those with a prior AUD. In adjusted analyses, male sex, past methamphetamine/crystal use, past marijuana use, past opioid/heroin use, past and current cocaine/crack use, and cigarette use were associated with a prior AUD. In conclusion, this study found that among non-drinking PLWH in routine clinical care, 36% had a prior AUD. We found key differences between those with and without prior AUD in demographic and clinical characteristics, including drug use and depression. These results suggest that non-drinkers are heterogeneous and need further differentiation in studies and that prior alcohol misuse (including alcohol treatment) should be included in behavioural health assessments as part of clinical care.